KEPENTINGAN INDONESIA MELARANG EKSPOR MINERAL NIKEL KE UNI EROPA - Ismail "; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Indonesia is the second largest nickel producer countries in the world after Russia. Nickel is a strategic raw material for the battery industry for electric cars, stainless steel, and others. This reasons led Indonesian government to take a different policy from the previous one by exporting in raw one. This research explained the reasons why Indonesian government stop for exporting nickel ore.This qualitative research used secondary data sources from books, journals, news from magazines and newspapers, official documents from the Indonesian government, and websites. To explain the reasons for the export ban, the author utilized a nation-state analysis with a mercantilism perspective, and the theory of economic nationalism.The results showed that the reason for this prohibition policy to increase strategic values, politically and economically. Politically, this policy is a countermeasure to increase bargaining power over discrimination against palm oil commodities by the European Union. Economically, the better nickel prices in the global market after the ban on nickel exports. The ban on nickel exports also encouraged better processed of domestic products into value-added comodities. Keywords: Mining, Nickel, Downstream, Investment, Minister of Energy and Mineral Resources Regulation No. 11 Year 2019